Penerapan Prinsip Ekonomi Syariah Sebagai Upaya Pendampingan dalam Mewujudkan Muamalah Al-Adabiyyah - Nurlaeli, Ida Nurlaeli; Maghfiroh, Siti; Ahsana, Kuntayuda (CV Litera Inti Aksara, 2025)
AbstractMuamalah maddiyah is a muamalah activity related to the fulfillment of material and wealth needs carried out by business people. This type of practice is known as economic activity. While muamalah al-adabiyyah is a muamalah activity related to the existence of bonds of norms, morals, and customary rules based on human values in the community environment, both must be carried out in a balanced manner, while in reality in Bumdes Pamijen and the Tobong Bata Community it has not been carried out in a balanced manner, so that it is contrary to the principles of Islamic economics. The purpose of this service is to formulate a strategy for implementing Islamic economic principles as an effort to assist in realizing muamalah al adabiyyah for BUMDes and the Red Brick Craftsman Community in Pamijen Village, Sokaraja District and to analyze what results will be achieved by BUMDes and the Red Brick Craftsman Community in Pamijen Village, Sokaraja District before and after implementing Islamic Economic Principles. The service method used is Community Based Research (CBR) as a research approach that involves the community as its partners. The results of the service include; Increasing understanding of Islamic business ethics in relation to muamalah al adabiyyah, Delivering material on Islamic business ethics and muamalah al adabiyyah accompanied by intensive mentoring, Increasing awareness of the importance of technology such as market place applications and the emergence of regeneration and high motivation in maintaining the balance of the world and the hereafter. Keywords: muamalah al adabiyyah, principles of sharia economics, laborers, tobong bata, BUMDES.